Order, Counter-order, Disorder : The Role of the IT Auditor in the Financial Statements Audit - Aubry, Manon (My University, 2021)
This thesis investigates the role of an IT auditor within a financial statements audit engagement. As the company’s information system environment evolves in tandem with the emergence of disrupting technologies, financial auditors cannot adapt their audit to suit these ever-more complex environments. Financial auditors increasingly resort to the employment of IT auditors to certify the integrity and reliability of the financial information emitted by information systems. It thus becomes pertinent to study the role adopted by an IT auditor during these engagements and to explore the dynamics of a working relationship. Therefore, this thesis seeks to define the role, duties and responsibility to IT auditors working with Financial auditors. In addition, the place of the IT auditor within the team and within the audit was inspected. For that purpose, a mixed-method case study was conducted via participant observation in a Big Four Audit Firm wherein the researcher took the role of an IT auditor-in-training. A process mining analysis on the formalization of the Planning and Conclusion workpapers of the IT audit complemented the research. The analyses contribute to a clearer understanding of the role and duties of the IT auditor during a financial statements audit. In addition, they uncover and seek to explain the dynamics between IT and Financial auditors. An established hierarchical team structure was highlighted throughout the results of the process mining analysis. The main conclusion reached by this thesis established the IT auditor as subservient to the Financial auditors with complex team dynamics. Within itself, the role of the auditor is flexible and adjustable to the different audit engagements, but the comprehension of the IT environment of the client and the applicable controls, IT general and IT applications controls, are as mandatory as the presentation of the conclusions to the Financial auditors.
Keywords: Auditing, Accounting, Big-4, Information System, IT Audit